What is the relationship between teaching approaches of instructors and learning approaches of teacher candidates? / Dilek İlhan-Beyaztas - İlhan-Beyaztas, Dilek (Universiti Teknologi MARA, 2019)
The aim of this study is to determine the relationship between the way that teacher candidates perceive the teaching approaches used by the instructors at the faculty of education and the learning approaches they prefer. The study group of this research was composed of 525 students from different departments of the faculty of education to determine the relationship between the teaching approaches and the learning approaches. As a result of the research, it was determined that the means of Information Transfer-Teacher - Focused (IT-TF) approach were higher than Conceptual Change-Student-Focused (CC-SF) scores across university departments and grade levels. It was also determined that the means of the deep and strategic learning approach across university departments, genders and grade levels were higher than the mean scores of the surface learning approach. In addition, there was a strong, positive and significant relationship between the mean score of IT-TF and the mean score of CC-SF, whereas it was found that there was a small, positive and significant relationship between the mean scores of IT-TF and CC-SF and DLA and SLA.